Identification of Metabolic Pathways Differentially Regulated in Somatic and Zygotic Embryos of Maritime Pine - Ávila, Concepción; Llebrés, María Teresa; Castro-Rodríguez, Vanessa; Lobato-Fernández, César; Reymond, Isabelle; Harvengt, Luc; Trontin, Jean-François; Cánovas, Francisco M. (Frontiers in Plant Science, 2022)
Embryogenesis is a complex phase of conifer development involving hundreds of genes, and a proper understanding of this process is critical not only to produce embryos with different applied purposes but also for comparative studies with angiosperms. A global view of transcriptome dynamics during pine somatic and zygotic embryogenesis is currently missing. Here, we present a genome-wide transcriptome analysis of somatic and zygotic embryos at three developmental stages to identify conserved biological processes and gene functions during late embryogenesis. Most of the differences became more significant as the developmental process progressed from early to cotyledonary stages, and a higher number of genes were differentially expressed in somatic than in zygotic embryos. Metabolic pathways substantially affected included those involved in amino acid biosynthesis and utilization, and this difference was already observable at early developmental stages. Overall, this effect was found to be independent of the line (genotype) used to produce the somatic embryos. Additionally, transcription factors differentially expressed in somatic versus zygotic embryos were analyzed. Some potential hub regulatory genes were identified that can provide clues as to what transcription factors are controlling the process and to how the observed differences between somatic and zygotic embryogenesis in conifers could be regulated.